Reasoning Hadith about the Day of Resurrection: A Critical Study of Atheism - Nashir Shihabudin; M. Yusuf Wibisono (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the refutation of the atheist argument about the absence of a resurrection day or life after death through hadith reasoning. This study applies a qualitative approach with the descriptive-reasoning method of hadith. The results and discussion of this study indicate that hadith reasoning is able to break the atheist view of the absence of a resurrection day through proof of text understanding and rational reasoning. This study concludes that the day of resurrection is a fact that can be proven by hadith reasoning and rational arguments. This study recommends the study of Islamic texts through syllogisms in providing a rebuttal to the atheism argument.